2012
DOI: 10.1186/1475-2840-11-148
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of recommended glucose and blood pressure targets in patients with type 2 diabetes and hypertension in clinical practice -- study rationale and protocol of DIALOGUE

Abstract: BackgroundPatients with type 2 diabetes have 2–4 times greater risk for cardiovascular morbidity and mortality than those without, and this is even further aggravated if they also suffer from hypertension. Unfortunately, less than one third of hypertensive diabetic patients meet blood pressure targets, and more than half fail to achieve target HbA1c values. Thus, appropriate blood pressure and glucose control are of utmost importance. Since treatment sometimes fails in clinical practice while clinical trials g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Diabetologists and primary care physicians were responsible for patient enrolment at centres selected in order to provide a representation of ambulatory care for patients with comorbid diabetes and hypertension. The study protocol, as well as primary and secondary objectives of DIALOGUE, have been previously published in detail [ 11 , 12 ]. DIALOGUE was registered in the database of the Verband forschender Arzneimittelhersteller ( http://www.vfa.de/de/arzneimittel-forschung/datenbanken-zu-arzneimitteln/nisdb ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetologists and primary care physicians were responsible for patient enrolment at centres selected in order to provide a representation of ambulatory care for patients with comorbid diabetes and hypertension. The study protocol, as well as primary and secondary objectives of DIALOGUE, have been previously published in detail [ 11 , 12 ]. DIALOGUE was registered in the database of the Verband forschender Arzneimittelhersteller ( http://www.vfa.de/de/arzneimittel-forschung/datenbanken-zu-arzneimitteln/nisdb ).…”
Section: Methodsmentioning
confidence: 99%
“…The DIALOGUE registry was established in order to evaluate differences in treatment strategies for patients with T2DM and comorbid hypertension, and to elucidate what factors influence the setting of individual targets in clinical practice [ 11 ]. In previous registry analysis, it was found that patients who had been set stricter target HbA1c levels were younger and less comorbid, while those with more lenient targets had a longer diabetes duration and were more likely to have heart failure (HF), peripheral artery disease (PAD), or neuropathy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ainda na presente pesquisa, observou--se que a comorbidade mais comumente encontrada foi o DM. A literatura aponta que a prevalência de hipertensos com DM é pelo menos duas vezes maior do que na população em geral e que devido às complicações agudas e crônicas as chances de o indivíduo sofrer com problemas cardiovasculares se elevam (16) . Outro agravante observado é que ocorre uma maior propensão do hipertenso ter dificuldade para aderir ao tratamento, pois aumenta o número de medicamentos prescritos e os cuidados com a dieta (17) .…”
Section: Discussionunclassified
“…The number of diabetic patients in China currently ranks first in the world according to the diabetes atlas of the International Diabetes Federation [ 2 ]. DM is a well-known risk factor for any form of cardiovascular disease (CVD) [ 3 ] and the risk for CVD of subjects with type 2 diabetes (T2DM) is 2 ~ fourfold higher than those without [ 4 ]. Hypertension (HTN) is prevailing in the complications of diabetes [ 5 ] and constitutes a critical challenge to the health burden as it elevates the prevalence of CVD, and this is even further aggravated if patients with concomitant T2DM [ 6 ].…”
Section: Introductionmentioning
confidence: 99%